Efforts of Competent PAI Teachers in Fostering Student Morals at SMP Muhammadiyah Imam Syuhodo for the 2023/2024 School Year - Prihamistu, Isna Hanan Noviantari (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research aims to determine the competency of PAI teachers and the efforts of PAI teachers in developing student morals at Muhammadiyah Imam Syuhodo Middle School. This type of research is descriptive qualitative research. Data collection uses observation, interview, and documentation techniques. The results of this research conclude that PAI teachers' efforts to develop the morals of Muhammadiyah Imam Syuhodo Middle School students are carried out in a unified manner, namely by all elements in the school, both educators and education staff. Methods and time allocation remain under the school system. Muhammadiyah Imam Syuhodo Middle School, most of its students come from the area around Muhammadiyah Imam Syuhodo Middle School. The education system is running quite well. Muhammadiyah Imam Syuhodo Middle School students in carrying out their worship of Allah, have carried it out well, applying good manners, being responsible, and caring for the surrounding environment. Even though some students have carried it out on their own without being ordered, some students still have to be ordered to carry it out.